KONDISI FISIK ATLET PERSATUAN ATLETIK SELURUH INDONESIA KABUPATEN KAYONG UTARA - Ardian Ardian; Andika Triansyah; Mimi Haetami (Universitas Tanjungpura, 2021)
AbstractThis research is based on the absence of an athlete data base on the level of physical condition of PASI athletic athletes in North Kayong Regency. This study intends to find out how big the level of physical condition of PASI athletes in North Kayong Regency. The test results of each component of different physical conditions, the results of each component are converted into T scores and added up. The components of the physical condition studied included the speed of leg muscle strength, arm and shoulder muscle strength, flexibility, and endurance. This type of research is a quantitative descriptive study, with a survey method with test and measurement data collection techniques. The population in this study were 14 athletes, consisting of 10 male athletes and 4 female athletes. This study uses a saturated sampling technique. The results of the research on the physical condition of PASI athletes in North Kayong Regency, which shows the results, for the